The Role Of Digital Block Chain Technology (Blockchain) In Reducing The Asymmetry Of Accounting Information With The Aim Of Supporting The Process Of Digital Transformation Of The Tax System In Syria"A Field Study" (Damascus University Journal for the economic and Political sciences, 2025)
Tthis study aimed to research The role played by digital block chain technology (Blockchain) in reducing the problem of asymmetry in accounting information with the aim of supporting the tax reform process in Syria. To achieve the objectives of the study, digital block chain technology was researched, its role in reducing the problem of information asymmetry, and its role in supporting the process of digital transformation of the tax system in Syria. A questionnaire was designed and directed to a sample of workers in the accounting field in Syrian companies, with varying academic degrees and years of experience. The study sample was (109) individuals, consisting of financial managers in companies, auditors in auditing offices and companies, a group of academics, and employees in the tax administration. The opinions and answers of the respondents were analyzed using statistical tests and the SPSS program, and the results were interpreted with the aim of testing the research hypothesis. The study reached a set of results, the most important of which is the existence of a positive, statistically significant relationship between the application of digital block chain technology (Blockchain) and reducing the phenomenon of asymmetric accounting information, and the application of Blockchain technology and supporting the process of digital transformation of the tax system in Syria.
Keywords: Blockchain Technology; Accounting information Asymmetry; Tax Reform Process